The origin of (so called) Open Brethrenism : a letter - Trotter, William, 1818-1865. (Kingston-on-Thames, UK : Stow Hill Bible and Tract Depot, 1849)
"The whole case of Plymouth and Bethesda."
Letter -- appendix.
Brethren writer
Keywords: Brethren movement -- divisions; The Bethesda question; Open brethren -- origins